Molar Mass and Molecular Weight Distribution Determination Of UHMWPE Synthesized Using a Living Homogeneous Catalyst - Saeid, Talebi; Rob, Duchateau; Sanjay, Rastogi; Peters, Gerrit; Kaschta, Joachim; Peters, Gerrit W. M.; Lemstra, Piet J. (Macromolecules, 2010)
Understanding of the physical characteristics of a polymer requires molar mass determination. For the commercially available polymers, having average molar mass below 1000000 g/mol, chromatography is the method that is often applied to determine the molar mass and molar mass distribution. However, the application of conventional chromatography techniques for polymers having molar mass > 1000 000 g/mol becomes very challenging, and often the results are disputed. In this article, melt rheometry based on the "modulus model" is utilized to measure the molar mass and polydispersity of ultra high-molecular-weight polyethylenes (UHMWPEs) having molar mass > 1000 000 g/mol. Results are compared with the chromatography data of the same polymer samples and the boundary conditions where the chromatography technique fails, whereas the rheometry provides the desired information is discussed. The rheological method is based on converting the relaxation spectrum from the time domain to the molecular weight domain and then Using a regularized integral inversion to recover the molecular weight distribution curve. The method is of relevance in determining very high molar masses (exceeding 3000000 g/mol) that cannot be ascertained conclusively with the existing chromatography techniques. For this study, UHMWPEs with various weight-average molar masses, where the number-average molar mass exceeds > 1000000 g/mol, are synthesized. Catalyst used for the synthesis is a living homogeneous catalyst system: MAO-activated bis(phenoxy imine) titanium dichloride. The rheological behavior of the thus synthesized nascent reactor powders confirms the disentangled state of the polymer that tends to entangle with time in mel